Analisis Keterampilan Perwira Jaga Terhadap Penggunaan Radar untuk Menghindari Terjadinya Kecelakaan di MT. Narpatisuta - Elysabet Br Sidauruk; Muhammad Sapril Siregar; Salfauqi Nurman (Journal on Education, 2023)
In carrying out a voyage, a ship has several navigational obstacles in terms of various conditions such as bad weather, narrow shipping lanes, black-outs, inadequate navigation equipment and lack of knowledge in operating navigation equipment. This study is aimed to know the skills of officers of the watch in using radar to avoid collisions in bad weather, narrow shipping lanes and black-outs. This study used a qualitative approach in which the data will be analyzed descriptively. Besides, the results of the analysis are also arranged to reveal about the development of teaching materials. In line with this opinion, this research can be developed in order to discuss the problems aboard the MT. Narpatisuta. The study show that: (1) The use of radar during bad weather are by using the gain, sea, rain tuner settings to adjust the strength of the radar signal and reduce the visibility disturbance from sea and rain conditions; (2) The use of radar when sailing in narrow shipping lanes can use EBL, VRM and Parallel Index to draw lines from ships to other objects, find out the distance between ships and the objects in vicinity and made several parallel lines to make it easier to sail in narrow shipping lane by keeping a distance from objects in vicinity; (3) In case of black-out, the radar screen must be monitored if there are dangers or other objects approaching, use all the features on the radar to avoid accidents and maximize radar operations such as sea, gain, rain, VRM, EBL and so forth.